ANALISIS PEMAHAMAN MAHASISWA DAN DOSEN MENGENAI ETIKA PROFESI AKUNTAN (Studi Kasus Pada Jurusan Akuntansi Universitas Islam Lamongan - Carmia Disa Cipta (Jurnal Akuntansi Indonesia, 2016)
Professional ethics are the principles that apply to a particular field. The principle of professional behavior requires every practitioner to comply with any laws and regulations, avoid any actions that may discredit the profession. Many of the problems that occur in ethics violations involving the accounting profession. One of these ethics violations by public accountants as the provision of an unqualified opinion on the financial statements that do not meet certain qualifications as per the norm Public Accountants Professional Standards. Ignore ethical action will not occur, if the student has an understanding of professional ethics, and ethics ignore actions will not occur if the lecturer can apply appropriate professional ethics. Researchers aimed to see the level of understanding and comprehension pebedaan between faculty (educators Accountant) and students (prospective accountant) about the ethics of accounting profession in the professional world. The population in this study were 133 respondents in the Islamic University Of Lamongan. Types of Research in this research is quantitative. The ingredients used are primary data obtained through questionnaires. Ingredients analyst using SPSS (Statistical Package for Social Science). The test method used is the test Validity, Reliability, Normality and Hypotheses using the Mann-Whitney test. These results indicate that there are significant differences between the level of student understanding and comprehension levels Accounting Accounting lecturer on Professional Ethics of Accountants.